2020
DOI: 10.1007/s00894-020-04603-1
|View full text |Cite
|
Sign up to set email alerts
|

Modelling the structural and reactivity landscapes of tucatinib with special reference to its wavefunction-dependent properties and screening for potential antiviral activity

Abstract: HER-2 type breast cancer is one of the most aggressive malignancies found in women. Tucatinib is recently developed and approved as a potential medicine to fight this disease. In this manuscript, we present the gross structural features of this compound and its reactivity and wave function properties using computational simulations. Density functional theory was used to optimise the ground state geometry of the molecule and molecular docking was used to predict biological activity. As the electrons interact wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(10 citation statements)
references
References 100 publications
(103 reference statements)
0
10
0
Order By: Relevance
“…In a study, Tucatinib, a drug developed for HER2-positive breast cancer, was repurposed against SARS-CoV-2. The docking results with the Mpro enzyme using PatchDock reported docking score of 5640 and ACE value of − 348.62 (Alsalme et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a study, Tucatinib, a drug developed for HER2-positive breast cancer, was repurposed against SARS-CoV-2. The docking results with the Mpro enzyme using PatchDock reported docking score of 5640 and ACE value of − 348.62 (Alsalme et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…Computational chemistry methods and bioinformatics tools are widely used in the field of drug design and for understanding the electronic properties of various drug-molecules [43][44][45][46][47][48]. Physicochemical property is an important parameter of a molecule that influences efficacy, safety or metabolism which could be predicted by using Lipinski's rule of five (RO5) that is: molecular mass < 500; Hydrogen-bond donors (HBD) ≤ 5; Hydrogen-bond acceptors (HBA) < 10; and Log P < 5 [49].…”
Section: Physicochemical Properties and Adme-t Profilesmentioning
confidence: 99%
“…The lopinavir, umifenovir, favipiravir, and oseltamivir molecules are also being studied as potentially active drugs against the virus [ 15 ]. Moreover, we have already reported that melatonin is active against this deadly virus [ 16 ] along with tucatinib [ 17 ] and selpercatinib [ 18 ]. Owing to the extensive time that is required to design and develop a drug to treat the virus, it is reasonable to reroute the existing drugs as molecular targets against the virus.…”
Section: Introductionmentioning
confidence: 99%